DIETARY TOXICITY TEST FOR 2% DRC-1339-TREATED BROWN RICE ON NONTARGET AVIAN SPECIES - Cummings, John L.; York, Darryl L.; Shively, Kirk J.; Pipas, Patricia A.; Stahl, Randal S.; Davis, James E., Jr. (DigitalCommons@University of Nebraska - Lincoln, 2003)
In Louisiana and Texas DRC-l339 treated brown rice is used to manage blackbird populations that cause severe damage to newly planted rice. Non-target bird species have been observed on some DRC-1339 bait sites. We conducted dietary toxicity tests to provide additional data on the toxicity of DRC-l339 to the following non-target species observed on DRC-1339 bait sites: savannah sparrows (Passerculus sandwichensis), Canada geese (Branta canadensis), snow geese (Chen caerulescens), mourning doves (Zenarda macroura), western meadowlarks (Sturnella neglecta), and American tree sparrows (Spizella arborea). During our 5-day DRC-1339 dietary test; in which birds were fed only 2% DRC-l339-treated brown rice diluted 1.25 with untreated brown rice, no mortality occurred to Canada geese or snow geese, and 1 mortality occurred to savannah sparrows. Nine of 10 mourning doves, 8 of 9 meadow larks and 8 of 10 American tree sparrows died during the same test. Most test species exhibited some degree of aversion to the DRC-1339 bait, indicating that in free-feeding situations such as DRC-1339 air sites most non-target birds might ingest sublethal doses and subsequently avoid treated baits. Rapid degradation and discoloration of DRC-1339 baits reduce the risk for non-target species at DRC-1339 bait sites.